Ratiometric Detection of Mercury (II) Ions in Living Cells Using Fluorescent Probe Based on Bis(styryl) Dye and Azadithia-15-Crown-5 Ether Receptor - Pavel A. Panchenko; Anastasija V. Efremenko; Alexey V. Feofanov; Mariya A. Ustimova; Yuri V. Fedorov; Olga A. Fedorova (Sensors, 2021)
Bis(styryl) dye 1 bearing N-phenylazadithia-15-crown-5 ether receptor has been evaluated as a ratiometric fluorescent chemosensor for mercury (II) ions in living cells. In aqueous solution, probe 1 selectively responds to the presence of Hg2+ via the changes in the emission intensity as well as in the emission band shape, which is a result of formation of the complex with 1:1 metal to ligand ratio (dissociation constant 0.56 ± 0.15 µM). The sensing mechanism is based on the interplay between the RET (resonance energy transfer) and ICT (intramolecular charge transfer) interactions occurring upon the UV/Vis (380 or 405 nm) photoexcitation of both styryl chromophores in probe 1. Bio-imaging studies revealed that the yellow (500–600 nm) to red (600–730 nm) fluorescence intensity ratio decreased from 4.4 ± 0.2 to 1.43 ± 0.10 when cells were exposed to increasing concentration of mercury (II) ions enabling ratiometric quantification of intracellular Hg2+ concentration in the 37 nM–1 μM range.